A comparative study on fibrinolytic in acute stroke patients in HUSM - Abdullah, Wan Zaidah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
The fibrinolytic system plays an important role in preventing intra-vascular thrombosis. Previous study bad shown the pathogenesis of stroke is related to abnormality in fibrinolytic system. This study was conducted in HUSM for a one-year period from March 2005 to February 2006. Stroke patients were selected from adult wards whereas control individuals were chosen from various clinics. This study was done to compare the levels of three fibrinolytic markers i.e. plasminogen (plg), tissue-plasminogen activator (t-PA) and plasminogen activator inhibitor type-I (PAI-l) between acute stroke patients and stable non-stroke individuals and to investigate the clinical significance of these markers. One hundred and six individuals and 51 acute stroke patients were selected. Both groups have similar risk factors. Their bloods were tested for the level of t-PA and PAl-l using EUSA technique (Biopool TintElize) whereas plasminogen was tested with colorimetric -··· . -· assay using Hemosil Tm. They were follow-up over a period of 3 months to detect their survival and lec;overy. We found only t-PA level was significantly higher in acute stro.k e patients compared to . control group even after adjusting the cofo~ders using ANCOV A test. Plasminogen and PAI-l showed no significant statistical association between both groups. For PAI-l, the mean level is lower in stroke group after adjusting the confounders. There are no significant statistical association between the three fibrinolytic markers and age, gender, manber of risk factors, disease severity, survival and neurological recovery. We observed all the eight patients who died dwing hospitalization or at the time of follow-up possessed high level oft-PA although statistically not significant. The limitation of this study was that we could not show the abnormality in t-PA is primary or secondary events to the development of stroke. High t-PA level indicates abnormal intravascular fibrinolysis which is probably an initiator ~f the-eerebrevaseular--- .. event or indicating of underlying vascular damage. This finding supports the hypothesis that disturbances in fibrinolysis occur in stroke patients during cerebrovascular event. We found an association between high t-PA antigen level and stroke with a 4.6-fold odd ratio. t-PA level could be a marker to predict high-risk patients for stroke development. Using haemOstatic model addressing fibrinolytic system is a potential discovery for future therapy to prevent acute episodes of stroke together with other therapeutic agents.